2013
DOI: 10.2961/jlmn.2013.03.0021
|View full text |Cite
|
Sign up to set email alerts
|

Laserscribing of Thin Films Using Top-Hat Laser Beam Profiles

Abstract: Ultrashort pulse lasers have been established as precise and universal tools for the micromachining of solid materials (cutting, texturing …). For these applications the quality of the cutting cross-section is important. The use of a Gaussian beam profile and linear polarization leads to tapered cutting sidewalls. It is possible to change the polarization orientation in order to machine a material for obtaining straight and vertical sidewalls. For this purpose a specific polarization converter was used. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…A beam that is shaped with FBS alters its beam profile during propagation. The diffraction-limited Top-Hat beam profile only appears at the focal position [4]. Hence, it is necessary to keep the distance between the focus lens and the machined material constant.…”
Section: Variation Of the Focal Positonmentioning
confidence: 99%
See 1 more Smart Citation
“…A beam that is shaped with FBS alters its beam profile during propagation. The diffraction-limited Top-Hat beam profile only appears at the focal position [4]. Hence, it is necessary to keep the distance between the focus lens and the machined material constant.…”
Section: Variation Of the Focal Positonmentioning
confidence: 99%
“…For thin film ablation with pulsed nanosecond lasers, the advantages of a spatially-optimized laser beam profile have been demonstrated in many studies [1][2][3][4][5]. In comparison to the common Gaussian beam profile with a circular footprint of Q-switched diode pumped solid state lasers (DPSSL), the use of a Top-Hat laser beam profile with a rectangular footprint provides several benefits for laser ablation of thin films (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Their research has shown a significant improvement in holes' quality, especially in drilling brass plates compared to a conventional Gaussian profile. In another investigation, a square top-hat beam was used to scribe 150 nm thin films of indium tin oxide using both refractive and diffractive beam shapers [42,43]. The uniform energy profile of the square top-hat beam allowed for a smaller pulse overlap to be used and this led to nine-fold increase in the scribing speed compared to Gaussian beam processing while achieving a similar quality.…”
Section: Application Of Top-hat Beams In Laser Micro-machiningmentioning
confidence: 99%
“…Additionally it can be favorable to convert the rotationally symmetric beam into a square or rectangular shape. 1,2 This reduces the time needed for pulsed laser scribing of lines since the overlap area of pulses can be reduced. Truncation of the beam would be another possibility to get a distribution close to homogeneous but this would lead to a high loss of laser power and unwanted diffraction effects.…”
Section: Introductionmentioning
confidence: 98%